Kajian Penilaian Kesehatan Dalam Rangka Mengevaluasi Kinerja Lembaga Keuangan Mikro Syariah Baitul Maal wat Tamwil (Kasus BMT Bina Umat Sejahtera Lasem Rembang) - - Aslichan; Musa Hubeis; Illah Sailah (Institut Pertanian Bogor, 2009)
One of model Micro Finance Institution (MFI) which in this one decade expand fast relative is Shariah MFI, the institutionthat more knowledgeable with Baitul Maal Wat Tamwil (BMT).Considering strategicvalue (BMT) and fact that assessment of performance of health BMT not yet done in this time, hence be conducted by this study/research at BMT Bina Umat Sejahtera (BUS) Lasem Rembang of Central Java. The aim of this study is know how the finance ratio influence performance of BMT BUS, that is factor of strength and its feebleness, also defining strategy needed in developing capacity of BMT BUS.This study conducted by (1) taking secondary datafrom financial statement of BMT BUS, literatures, journals, bulletins, and seminar paper, (2) direct observation at BMT checked, (3) and interview. Quantitative data analysis is done by blend analysis of finance performance assessment, a kind of CAMEL (Capital, Assets, Management, Earning, and Liquidity) for banking with ratio of efficiency and rentability from ratio sum up staff approach.So that this component assessment consists of capital structure ratio, solvabilitas, productive asset quality, liquidity, efficiency, rentability, independency and sustainability. The result depicted in radar chart graph. To sharpen analysis used with Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis. Result posed in this study is that Healthy Performance BMT Bina Umat Sejahtera in the year 2006 inclusive of category of well enough, with its strength component ( score 4) in stories; level of financing risk of a period of to small, very efficient in optimalise of Account Officer staff ( AO) in serving customer financing, very able to activate society for funding and optimalise in portfolio financing, very self-supporting in operational cost, and very able to manage outstanding financing with existing AO staff. There is factor of feebleness of BMT BUS (score 1) there is [at] abolition reserve of risk financing smaller thanrisk financing which owning, alocate too high asset fixed asset, and its ability get net profit very minimize compared to by a asset and or the capital managed its.